2003
DOI: 10.1098/rstb.2003.1307
|View full text |Cite
|
Sign up to set email alerts
|

Abstraction in art with implications for perception

Abstract: The relationship between people and art is complex and intriguing. Of course, artworks are our creations; but in interesting and important ways, we are also created by our artworks. Our sense of the world is informed by the art we make and by the art we inherit and value, works that, in themselves, encode others' world views. This two-way effect is deeply rooted and art encodes and affects both a culture's ways of perceiving the world and its ways of remaking the world it perceives. The purpose of this paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…It is generally assumed that abstraction is a built-in process typical to people’s way of thinking (see Root-Bernstein, 2001 ; Zimmer, 2003 ; Gray and Tall, 2007 ; Henriksen et al, 2014 ). The processes of categorization and classification such as grouping a dancer, a child, and a man sitting in a chair under the category of “human” inevitably involve abstraction, because they seek to preserve certain features shared by these objects while ignoring other features of these individuals.…”
Section: On Abstractionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally assumed that abstraction is a built-in process typical to people’s way of thinking (see Root-Bernstein, 2001 ; Zimmer, 2003 ; Gray and Tall, 2007 ; Henriksen et al, 2014 ). The processes of categorization and classification such as grouping a dancer, a child, and a man sitting in a chair under the category of “human” inevitably involve abstraction, because they seek to preserve certain features shared by these objects while ignoring other features of these individuals.…”
Section: On Abstractionmentioning
confidence: 99%
“…The processes of categorization and classification such as grouping a dancer, a child, and a man sitting in a chair under the category of “human” inevitably involve abstraction, because they seek to preserve certain features shared by these objects while ignoring other features of these individuals. From this point of view, all art, including figurative painting, implements some degree of abstraction because it is never an accurate representation of reality per se ( Gortais, 2003 ; Zimmer, 2003 ). Gray and Tall (2007) suggested that the abstraction process is governed by the compression of knowledge into thinkable concepts, which yields a more sophisticated way of apprehending these concepts.…”
Section: On Abstractionmentioning
confidence: 99%
See 1 more Smart Citation
“…This characteristic is still prevalent in abstract art today and most often presented through the rubric of language: the grammar of abstract art. Despite this, as Robert Zimmer (2003Zimmer ( : 1286 rightly notes:…”
Section: Kaleidoscopic Abstractionmentioning
confidence: 99%
“…Abstraction allows artists to uncover the fundamental components or essence of an object. Some artists have also suggested that what is often labelled as "abstract" is in fact a 'more concrete version of our mental constructs' (Zimmer 2003(Zimmer , 1286. In a similar vein, Walter Benjamin (1892Benjamin ( -1940 describes how cinema and photography can record aspects of reality outside of the range of normal human perception and becomes an avenue for experiencing the 'optical unconscious' (Benjamin 2000, p. 14-16).…”
Section: Decentralisationmentioning
confidence: 99%